Biomechanical analysis of the technique of performing competitive exercises in rhythmic gymnastics using the example of the “panche” balance - Smyrnova , Olha; Gamalii, Volodymyr (Sportyvnyi Visnyk Prydniprovia, 2026)
Purpose of the study: to determine the biomechanical parameters of the technique of performing the “penché” balance by gymnasts at the stage of preliminary basic training. Materials and methods. The study involved 28 gymnasts aged 8–12 years at the stage of preliminary basic training. To analyze the technique of performing the element, an optoelectronic motion capture system “Qualisys” and a force platform «Kistler» were used. The duration of the key phase of the element, amplitude, frequency, and mean velocity of center of pressure (COP) oscillations in the sagittal and frontal planes, as well as angular characteristics (split angle and trunk inclination angle), were measured. Statistical analysis was performed using descriptive statistics. Results. It was found that the mean duration of the “releve stand” phase meets the competition requirements but demonstrates considerable variability. Functional differences in COP oscillation patterns between the dominant and non-dominant leg were identified: for the right leg, larger sagittal amplitude, frequency, and velocity of oscillations were observed, whereas when supporting on the left leg, increased amplitude and velocity were seen in the frontal plane, while sagittal oscillations showed a higher frequency. The split angle on the right leg was at the upper limit of acceptable values, while on the left leg it was below the normative requirement, making the element unacceptable for scoring without penalties. Conclusions. The obtained biomechanical parameters indicate the presence of functional asymmetry in postural control among the gymnasts and allow for an objective assessment of the technique of performing the “penché” balance. The application of biomechanical analysis provides a basis for targeted correction of the training process and improvement of the quality of competitive performance.